2018
DOI: 10.7287/peerj.preprints.26816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of antioxidant properties of membrane ultrafiltration peptides from mungbean meal protein hydrolysates

Abstract: Background Bioactive peptides can prevent damage associated with oxidative stress in the human body when consumed regularly. Recently year, peptides have attracted immense interest because of their beneficial functional properties, safety and little or no side effects when used at high concentration. Most antioxidant peptide has small size less than 1 kDa and contains high proportion of hydrophobic amino acid. Particularly Tyr, Leu, Ala, Ile, Val, Lys, Phe, Cys, Met and His exhibited high antioxidant activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(41 reference statements)
2
3
2
Order By: Relevance
“…Sonklin et al. (2018) obtained contrasting HRSA results to that of our study and reported 98.7% (GSH), 54.5% (<1 kDa) and 49.6% (>10 kDa), which are significantly ( p < .05) higher than data obtained in the current study. However, the HRSA of 27.0% (1–5 kDa) and 35.2% (5–10 kDa) reported for the mung bean peptides are similar in magnitude to the values for same sesame peptide fractions.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Sonklin et al. (2018) obtained contrasting HRSA results to that of our study and reported 98.7% (GSH), 54.5% (<1 kDa) and 49.6% (>10 kDa), which are significantly ( p < .05) higher than data obtained in the current study. However, the HRSA of 27.0% (1–5 kDa) and 35.2% (5–10 kDa) reported for the mung bean peptides are similar in magnitude to the values for same sesame peptide fractions.…”
Section: Resultscontrasting
confidence: 99%
“…The ability to scavenge superoxide radicals by sesame proteins and peptides will be beneficial in reducing the amount of hydroxyl radicals produced, which are the most hazardous to cellular organelles. The SRSA results in this study showing that the HMW, 5–10 kDa sesame peptides had the highest value of 84% contrasted a previous report (Sonklin et al., 2018) in which, mung bean 1 kDa peptide fraction exhibited the strongest activity (65.1% ) compared to the HMW fractions with SRSA of < 50.0%. Peng et al.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…Most antioxidant peptides are low molecular weight (<1 kDa) and contain a high proportion of hydrophobic amino acid. These amino acids act as antioxidants by increasing the solubility of peptides in non‐polar environments, thereby facilitating better interaction with free radicals in order to terminate their activities . Several researchers have suggested that low‐molecular‐weight peptides enriched by ultrafiltration can easily cross the intestinal barrier to exert biological effects and interact with targets …”
Section: Resultsmentioning
confidence: 99%